A Cyclodextrin‐Stabilized Spermine‐Tagged Drug Triplex that Targets Theophylline to the Lungs Selectively in Respiratory Emergency. Issue 12 (25th September 2020) - Sofian, Zarif M.; Benaouda, Faiza; Wang, Julie Tzu‐Wen; Lu, Yuan; Barlow, David J.; Royall, Paul G.; Farag, Doaa B.; Rahman, Khondaker Miraz; Al‐Jamal, Khuloud T.; Forbes, Ben; Jones, Stuart A.
Abstract: Ion‐pairing a lifesaving drug such as theophylline with a targeting moiety could have a significant impact on medical emergencies such as status asthmaticus or COVID‐19 induced pneumomediastinum. However, to achieve rapid drug targeting in vivo the ion‐pair must be protected against breakdown before the entry into the target tissue. This study aims to investigate if inserting theophylline, when ion‐paired to the polyamine transporter substrate spermine, into a cyclodextrin (CD), to form a triplex, could direct the bronchodilator to the lungs selectively after intravenous administration. NMR demonstrates that upon the formation of the triplex spermine protruded from the CD cavity and this results in energy‐dependent uptake in A549 cells (1.8‐fold enhancement), which persists for more than 20 min. In vivo, the triplex produces a 2.4‐fold and 2.2‐fold increase in theophylline in the lungs 20 min after injection in rats and mice, respectively ( p < 0.05). The lung targeting is selective with no increase in uptake into the brain or the heart where the side‐effects of theophylline are treatment‐limiting. Selectively doubling the concentration of theophylline in the lungs could improve the benefit‐risk ratio of this narrow therapeutic index medicine, which continues to be important in critical care. Abstract : This article demonstrates that ion‐pairing theophylline, a drug used in medical emergencies such as status asthmaticus or COVID‐19 induced pneumomediastinum, with a polyamine, can direct delivery to the lung. Such an approach is effective when the ion‐pair is stabilized as a triplex with cyclodextrin, which increases the in vivo ion‐pair life‐time to facilitate active accumulation in the lung.